Thermal cameras in school laboratory activities. (19th June 2015) - Haglund, Jesper; Jeppsson, Fredrik; Hedberg, David; Schönborn, Konrad J
Abstract: Thermal cameras offer real-time visual access to otherwise invisible thermal phenomena, which are conceptually demanding for learners during traditional teaching. We present three studies of students' conduction of laboratory activities that employ thermal cameras to teach challenging thermal concepts in grades 4, 7 and 10–12. Visualization of heat-related phenomena in combination with predict-observe-explain experiments offers students and teachers a pedagogically powerful means for unveiling abstract yet fundamental physics concepts.